The supervision of strategy and risk in German two-tier boards: lessons learned from the crisis. (2013) - Eulerich, Marc; Stiglbauer, Markus
The boards' role to supervise corporate strategy and risk determines the efficiency of 'good' corporate governance. Not only in the highlight of the financial crisis, board members, are challenged by a critical need for pro-active supervision. We examine the effects of the crisis on German supervisory boards' work and conclude first, which supervisory boards work in a pro-active way: They support the executive board in strategy development and implementation and try to anticipate the strategic development of the company. Secondly, boards change their meeting schedule immediately in case of a potential crisis. Thirdly, besides the focus on financial data, board members use other sources of information and a stakeholder perspective as an important source to supervise the executive board's work.